Time discounting for primary rewards - McClure, Samuel M; Ericson, Keith M; Laibson, David I; Loewenstein, George; Cohen, Jonathan D (The Journal of neuroscience, 2007)
Previous research, involving monetary rewards, found that limbic reward-related areas show greater activity when an intertemporal choice includes an immediate reward than when the options include only delayed rewards. In contrast, the lateral prefrontal and parietal cortex (areas commonly associated with deliberative cognitive processes, including future planning) respond to intertemporal choices in general but do not exhibit sensitivity to immediacy (McClure et al., 2004). The current experiments extend these findings to primary rewards (fruit juice or water) and time delays of minutes instead of weeks. Thirsty subjects choose between small volumes of drinks delivered at precise times during the experiment (e.g., 2 ml now vs 3 ml in 5 min). Consistent with previous findings, limbic activation was greater for choices between an immediate reward and a delayed reward than for choices between two delayed rewards, whereas the lateral prefrontal cortex and posterior parietal cortex responded similarly whether choices were between an immediate and a delayed reward or between two delayed rewards. Moreover, relative activation of the two sets of brain regions predicts actual choice behavior. A second experiment finds that when the delivery of all rewards is offset by 10 min (so that the earliest available juice reward in any choice is 10 min), no differential activity is observed in limbic reward-related areas for choices involving the earliest versus only more delayed rewards. We discuss implications of this finding for differences between primary and secondary rewards.